Phenotypic correction of Fanconi anemia in human hematopoietic cells with a recombinant adeno-associated virus vector. - Walsh, C E (1994)
Fanconi anemia (FA) is a recessive inherited disease characterized by defective DNA repair. FA cells are hypersensitive to DNA cross-linking agents that cause chromosomal instability and cell death. FA is manifested clinically by progressive pancytopenia, variable physical anomalies, and predisposition to malignancy. Four complementation groups have been identified, termed A, B, C, and D. The gene for the FA complementation group C, FACC, has been cloned. Expression of the FACC cDNA corrects the phenotypic defect of FA(C) cells, resulting in normalized cell growth in the presence of DNA cross-linking agents such as mitomycin C (MMC). Gene transfer of the FACC gene should provide a survival advantage to transduced hematopoietic cells, suggesting that FA might be an ideal candidate for gene therapy. We demonstrated efficient transduction, expression, and phenotypic correction in lymphoblastoid cell lines derived from FA (C) patients using a recombinant adeno-associated virus (rAAV) vector containing the FACC gene. Molecular characterization of the transduced FACC gene showed an intact unrearranged proviral genome with expression sufficient to normalize cell growth, cell cycle kinetics and chromosomal breakage in the presence of MMC. These observations were extended by testing rAAV transduction in hematopoietic progenitor cells. Peripheral blood CD34+ cells isolated from a FA (C) patient and transduced with rAAV/FACC virus yielded 5-10-fold more progenitor colonies than mock-infected cells, consistent with genetic "rescue" of corrected cells. This is the first demonstration of rAAV gene correction in primary human hematopoietic progenitor cells and has important implications for gene therapy of hematopoietic disorders, specifically FA.